On the Choice and the Effects of Rule-Based Contribution Schemes in Public Good Games - Carlo Gallier; Martin Kesternich; Bodo Sturm (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In this experiment, we endogenize the choice of which contribution scheme is implemented in a public good game. We investigate three rule-based contribution schemes and a voluntary contribution mechanism (VCM). The game is implemented either as a Single- or a Multi-Phase Game. In the Single-Phase Game, the contribution schemes are exogenously implemented. In the Multi-Phase Game, we let subjects vote on the rule-based contribution schemes. If a scheme gets a sufficient majority it is implemented. In case a sufficient majority is failed, subjects have to make their contributions to the public good using the VCM. We find that the endogenous choice of a contribution scheme has an impact on the level of contributions. In case of a rule-based contribution scheme which equalizes payoffs, contributions are higher if subjects chose the scheme for themselves than in case the scheme is implemented exogenously. The contrary holds for the VCM. Contributions are higher if the VCM is implemented exogenously than in case a sufficient majority is failed and, therefore, subjects have to play the VCM.
Keywords: C72; C92; H41; 330